set n = 1;
let f be V22() standard special_circular_sequence; :: thesis: for p being Point of () st p in rng f holds
left_cell (f,(p .. f)) = left_cell ((Rotate (f,p)),1)

let p be Point of (); :: thesis: ( p in rng f implies left_cell (f,(p .. f)) = left_cell ((Rotate (f,p)),1) )
assume A1: p in rng f ; :: thesis: left_cell (f,(p .. f)) = left_cell ((Rotate (f,p)),1)
set k = p .. f;
len f > 1 by ;
then p .. f < len f by ;
then A2: (p .. f) + 1 <= len f by NAT_1:13;
A3: 1 <= p .. f by ;
A4: for i1, j1, i2, j2 being Nat st [i1,j1] in Indices (GoB (Rotate (f,p))) & [i2,j2] in Indices (GoB (Rotate (f,p))) & (Rotate (f,p)) /. 1 = (GoB (Rotate (f,p))) * (i1,j1) & (Rotate (f,p)) /. (1 + 1) = (GoB (Rotate (f,p))) * (i2,j2) & not ( i1 = i2 & j1 + 1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),(i1 -' 1),j1) ) & not ( i1 + 1 = i2 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j1) ) & not ( i1 = i2 + 1 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i2,(j2 -' 1)) ) holds
( i1 = i2 & j1 = j2 + 1 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j2) )
proof
(Rotate (f,p)) /. (((1 + 1) + (p .. f)) -' (p .. f)) = (Rotate (f,p)) /. (1 + 1) by NAT_D:34;
then A5: (Rotate (f,p)) /. ((((p .. f) + 1) + 1) -' (p .. f)) = (Rotate (f,p)) /. (1 + 1) ;
A6: left_cell (f,(p .. f)) = left_cell (f,(p .. f)) ;
let i1, j1, i2, j2 be Nat; :: thesis: ( [i1,j1] in Indices (GoB (Rotate (f,p))) & [i2,j2] in Indices (GoB (Rotate (f,p))) & (Rotate (f,p)) /. 1 = (GoB (Rotate (f,p))) * (i1,j1) & (Rotate (f,p)) /. (1 + 1) = (GoB (Rotate (f,p))) * (i2,j2) & not ( i1 = i2 & j1 + 1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),(i1 -' 1),j1) ) & not ( i1 + 1 = i2 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j1) ) & not ( i1 = i2 + 1 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i2,(j2 -' 1)) ) implies ( i1 = i2 & j1 = j2 + 1 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j2) ) )
assume that
A7: ( [i1,j1] in Indices (GoB (Rotate (f,p))) & [i2,j2] in Indices (GoB (Rotate (f,p))) ) and
A8: (Rotate (f,p)) /. 1 = (GoB (Rotate (f,p))) * (i1,j1) and
A9: (Rotate (f,p)) /. (1 + 1) = (GoB (Rotate (f,p))) * (i2,j2) ; :: thesis: ( ( i1 = i2 & j1 + 1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),(i1 -' 1),j1) ) or ( i1 + 1 = i2 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j1) ) or ( i1 = i2 + 1 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i2,(j2 -' 1)) ) or ( i1 = i2 & j1 = j2 + 1 & left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j2) ) )
A10: GoB (Rotate (f,p)) = GoB f by REVROT_1:28;
len (Rotate (f,p)) = len f by FINSEQ_6:179;
then (Rotate (f,p)) /. (len f) = (Rotate (f,p)) /. 1 by FINSEQ_6:def 1;
then (Rotate (f,p)) /. (((p .. f) + (len f)) -' (p .. f)) = (Rotate (f,p)) /. 1 by NAT_D:34;
then A11: f /. (p .. f) = (GoB f) * (i1,j1) by ;
p .. f < (p .. f) + 1 by NAT_1:13;
then A12: f /. ((p .. f) + 1) = (GoB f) * (i2,j2) by ;
then A13: ( ( i1 = i2 & j1 + 1 = j2 & left_cell (f,(p .. f)) = cell ((GoB f),(i1 -' 1),j1) ) or ( i1 + 1 = i2 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB f),i1,j1) ) or ( i1 = i2 + 1 & j1 = j2 & left_cell (f,(p .. f)) = cell ((GoB f),i2,(j2 -' 1)) ) or ( i1 = i2 & j1 = j2 + 1 & left_cell (f,(p .. f)) = cell ((GoB f),i1,j2) ) ) by ;
per cases ( ( i1 = i2 & j1 + 1 = j2 ) or ( i1 + 1 = i2 & j1 = j2 ) or ( i1 = i2 + 1 & j1 = j2 ) or ( i1 = i2 & j1 = j2 + 1 ) ) by ;
case ( i1 = i2 & j1 + 1 = j2 ) ; :: thesis: left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),(i1 -' 1),j1)
hence left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),(i1 -' 1),j1) by ; :: thesis: verum
end;
case ( i1 + 1 = i2 & j1 = j2 ) ; :: thesis: left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j1)
hence left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j1) by ; :: thesis: verum
end;
case ( i1 = i2 + 1 & j1 = j2 ) ; :: thesis: left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i2,(j2 -' 1))
hence left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i2,(j2 -' 1)) by ; :: thesis: verum
end;
case ( i1 = i2 & j1 = j2 + 1 ) ; :: thesis: left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j2)
hence left_cell (f,(p .. f)) = cell ((GoB (Rotate (f,p))),i1,j2) by ; :: thesis: verum
end;
end;
end;
1 + 1 <= len (Rotate (f,p)) by ;
hence left_cell (f,(p .. f)) = left_cell ((Rotate (f,p)),1) by ; :: thesis: verum